The Patch Formulation of Rambusa (Passiflora foetida) Leave Extract as Anti-Inflammatory Agent: An In Vitro and In Vivo Study - Lindawati Setyaningrum; Aliyah Purwanti; Widaddhiya Zahra Anggraini; Adelia Royan Suryani; Tolak Haris; Lubis Nuril Ubaidilla (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2024)
Rambusa leaves are known to have health benefits, including anti-inflammatory, antitumor, anticancer, antihepatotoxicity and antimicrobial. Rambusa leaves contain active compounds including alkaloids, tannins, saponins, and steroids which have anti-inflammatory effects. So it was developed as a transdermal route preparation in the form of a patch to overcome the problem of side effects from using oral medications on the gastrointestinal tract. Rambusa leaves are formulated into additional ingredients in the form of HPMC, methyl paraben, propylene glycol, 96% ethanol, distilled water and made into ready-to-use patches. Furthermore, an evaluation of the physical quality of the formula was carried out and its anti-inflammatory effectiveness was determined through in vitro and in vivo tests. The results show that each formula produces physical properties that meet the requirements. Apart from that, the results of the in vitro test using sodium diclofenac as a standard show that formulas 100, 200 and 300 are able to penetrate the membrane from the results of the cumulative amount of active ingredients that have been tested, whereas in the in vivo test using wistar rat test, the results of % edema were analyzed using ANOVA and the results of % inhibition were carried out in a post hoc test with LSD. The highest effectiveness was obtained in formula 300, this shows that the formula is capable of inhibiting inflammation. From these results it can be concluded that rambusa leave extract can be developed into a transdermal patch formula for anti-inflammation.